Comparative molecular dynamic studies of psychrophilic leucine dehydrogenase with corresponding mesophilic and thermophilic homologous - Nur Afizah Samat, 1991- 605105 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2014)
Project Paper (Sarjana Muda Sains (Biologi)) - Universiti Teknologi Malaysia, 2014